Despite the Odds: Factors Related to the Academic Success of First Grade Students From At-Risk Backgrounds (LEARNing Landscapes, 2013)
Research indicates that family income and linguistic background are related to students’ academic achievement, as evidenced by the gaps in the academic achievement levels of children from families with high or low income, and children with English as their first or additional language. However, there are students who succeed despite these risk factors. In this qualitative study, we interviewed two cohorts of parents who had first-grade children doing well in school. Even with the limited sample size, there were some consistent patterns in the environments of these children, namely, warm parenting with boundaries; academic capital in the home; thoughtful guidance of activities at home; close-knit family; and positive experiences at school.
Keywords: academic achievement; linguistic background; family income; qualitative; interview; environment; parenting; academic capital